Factors Affecting Banking Stock Price on the Indonesian Stock Exchange 2017 to 2021 - Pujangga, Fatwa; Handrijaningsih, Lies (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to ascertain the impact of the factors named Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Return on Assets (ROA), and Loan to Deposit Ratio (LDR). Both simultaneously and partially on banking stock prices on the Indonesia Stock Exchange (IDX) in the period (2017-2021). The analysis method used in this study is Multiple Linear Regression Analysis using a Statistical Analysis tool in the form of SPSS. The results of simultaneous hypothesis testing of independent variables consisting of LDR, ROA, NPL and CAR affect Stock Prices. Stock prices are unaffected by the findings of the LDR partial hypothesis test. Stock prices are significantly impacted by the findings of the partial hypothesis testing of ROA. Stock prices are unaffected by the partial hypothesis testing outcomes for NPL. Stock prices are unaffected by the findings of the CAR partial hypothesis test.